1980
DOI: 10.1002/cne.901890106
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for the guidance and topographic patterning of retinal ganglion cell axons

Abstract: Three dimensional reconstruction, with the use of serial, 1-micrometer sections, has revealed a system of oriented intercellular spaces within the undifferentiated optic cup. These large openings appear in the marginal zone of the primitive retina and optic stalk prior to the formation of the first retinal ganglion cell axons. The spaces at the region of the optic disc form sets of long, interconnecting tunnels oriented in the direction of the stalk. The spaces at the back and rim of the cup form blind, radial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
95
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(100 citation statements)
references
References 26 publications
5
95
0
Order By: Relevance
“…In newt spinal cord (Singer et al, 1979), it has been shown in electron micrographs that rostro-caudally oriented spaces between columns of cells in the spinal cord are packed with axons as development progresses. In mouse retina, Silver and Robb (1979) have shown that intercellular channels appear to be routes for outgrowth of optic nerve fibres, and serial sections through the developing retina show that the orientation of these channels is consistent with that of the later growing axons (Silver and Sidman, 1980). Other studies in chick spinal cord have demonstrated a relationship between extracellular spaces and axonal extension, but as in the present study, have not addressed the question of whether there is a specific signaling mechanism between extracellular matrix and growth cones or axons.…”
Section: Discussionmentioning
confidence: 97%
“…In newt spinal cord (Singer et al, 1979), it has been shown in electron micrographs that rostro-caudally oriented spaces between columns of cells in the spinal cord are packed with axons as development progresses. In mouse retina, Silver and Robb (1979) have shown that intercellular channels appear to be routes for outgrowth of optic nerve fibres, and serial sections through the developing retina show that the orientation of these channels is consistent with that of the later growing axons (Silver and Sidman, 1980). Other studies in chick spinal cord have demonstrated a relationship between extracellular spaces and axonal extension, but as in the present study, have not addressed the question of whether there is a specific signaling mechanism between extracellular matrix and growth cones or axons.…”
Section: Discussionmentioning
confidence: 97%
“…CSPG may be synthesised by the immature radial glia at rhombomere boundaries, participating in the formation of the large intercellular spaces. Spaces between glial endfeet have been implicated as axon guidance channels in newts (Singer et al, 1979), and also in the developing mouse retina (Silver and Sidman, 1980). In rat spinal cord, specialised glia-like cells of the floor plate attract commissural axons (Tessier-Lavigne et al, 19881, and are known to express the putative chemoattractant netrin-1 Kennedy et al, 1994).…”
Section: Radial Glia At Rhombomere Boundaries As Axon Guidesmentioning
confidence: 99%
“…It has been well established that, in the injured as well as in the intact developing brain, the growth of axons occurs in the presence of astrocytes that may serve as guides (Schmechel and Rakic, 1979;Silver and Sidman, 1980;Silver et al, 1993). In contrast, regrowth of axotomized axons does not occur in the adult brain, and in this regard the inhibitory role of the astroglial scar has been well documented (for review, see Reier, 1986;Reier and Houle, 1988).…”
mentioning
confidence: 99%